Morfometrik dan Meristik Ikan Kelabau (Osteochilus melanopleurus) dari Sungai Kampar, Provinsi Riau - Asiah, Nur; Junianto, Junianto; Yustiati, Ayi; Sukendi, Sukendi (Jurnal Perikanan dan Kelautan, 2018)
Osteochilus melanopleurus or kalabau fish is indigenous fish of the Kampar River,Riau. The information on morphological and meristical characteristics of this fish,however, is almost none. To understand the morphological and meristical characteristicsof the fish, a study has been conducted from April to September 2017. The fishwas sampled using fish trap and nets (1.15 cm and 5 cm mesh size). Twenty one characteristicswere measured using a Vernier calliper and then each character was comparedto Standard Length (SL). There were 96 fishes captured, consist of 59 males(160-355 mm SL, 100-1800 g BW), 22 females (310-515 mm SL, 850-4000 g BW)and 15 juveniles (80 -180 mm SL, 11.50- 194 g BW). In general, there was no differencecharacteristics in male and female fish. The distance between mouth lip to pectoralfin was around 51% of SL; dorsal fin to pelvic fin was around 39% of SL; dorsalback to caudal bottom was around 28 % of SL and anal fin back was around 21 % ofSL and TL was around 130% of SL. Meristical characteristics of fish are as follows: D.II. 151/2-191/2 ; P. I. 14-17; V. I.8; A.II.61/2; C.VI.6.II. The sex of juveniles, however,could not be identified as gonad in this young fish was not developed yet. Based ondata obtained, it can be concluded that the relative growth of all characteristics measuredwere almost isometric to SL.